simplify
![3 \sqrt{2} + \sqrt{18} - 1 \div 2 \sqrt{8} = 3 \sqrt{2} + \sqrt{18} - 1 \div 2 \sqrt{8} =](https://tex.z-dn.net/?f=3+%5Csqrt%7B2%7D++%2B++%5Csqrt%7B18%7D++-+1+%5Cdiv+2+%5Csqrt%7B8%7D++%3D++)
Answers
Answered by
3
Hello Friend ✋✋✋
Your answer.....
= ( 3√2 + 3√2 - 1 ) / 4√2
= (6√2 -1 )/4√2
Rationalising denominator......
= √2 × ( 6√2 -1 )/ ( √2 × 4√2 )
= ( 12 - √2 ) / 8
Hope it helps
Your answer.....
= ( 3√2 + 3√2 - 1 ) / 4√2
= (6√2 -1 )/4√2
Rationalising denominator......
= √2 × ( 6√2 -1 )/ ( √2 × 4√2 )
= ( 12 - √2 ) / 8
Hope it helps
Golu2001:
bhai ye answer wrong h
Answered by
0
May be the answer is.....
![\frac{3 \sqrt{2} + \sqrt{18} - 1 }{2 \sqrt{8} } \\ = \frac{3 \sqrt{2} + 3 \sqrt{2} - 1 }{2 \sqrt{8} } \\ = \frac{(6 \sqrt{2} - 1) }{2 \times 2 \sqrt{2} } \\ = \frac{(6 \sqrt{2 } - 1 )}{4 \sqrt{2} } \\ = \frac{4 \sqrt{2}( 6 \sqrt{2} - 1) }{32} \\ = \frac{48 - 4 \sqrt{2} }{32} \\ = \frac{4(12 - \sqrt{2} )}{32} \\ = \frac{(12 - \sqrt{2}) }{8} \frac{3 \sqrt{2} + \sqrt{18} - 1 }{2 \sqrt{8} } \\ = \frac{3 \sqrt{2} + 3 \sqrt{2} - 1 }{2 \sqrt{8} } \\ = \frac{(6 \sqrt{2} - 1) }{2 \times 2 \sqrt{2} } \\ = \frac{(6 \sqrt{2 } - 1 )}{4 \sqrt{2} } \\ = \frac{4 \sqrt{2}( 6 \sqrt{2} - 1) }{32} \\ = \frac{48 - 4 \sqrt{2} }{32} \\ = \frac{4(12 - \sqrt{2} )}{32} \\ = \frac{(12 - \sqrt{2}) }{8}](https://tex.z-dn.net/?f=+%5Cfrac%7B3+%5Csqrt%7B2%7D+%2B++%5Csqrt%7B18%7D+-+1++%7D%7B2+%5Csqrt%7B8%7D+%7D++%5C%5C++%3D++%5Cfrac%7B3+%5Csqrt%7B2%7D+%2B+3+%5Csqrt%7B2%7D+-+1++%7D%7B2+%5Csqrt%7B8%7D+%7D++%5C%5C++%3D++%5Cfrac%7B%286+%5Csqrt%7B2%7D+-+1%29+%7D%7B2+%5Ctimes+2+%5Csqrt%7B2%7D+%7D++%5C%5C++%3D++%5Cfrac%7B%286+%5Csqrt%7B2+%7D+-+1+%29%7D%7B4+%5Csqrt%7B2%7D+%7D++%5C%5C++%3D++%5Cfrac%7B4+%5Csqrt%7B2%7D%28+6+%5Csqrt%7B2%7D+-+1%29+%7D%7B32%7D++%5C%5C++%3D++%5Cfrac%7B48+-+4+%5Csqrt%7B2%7D+%7D%7B32%7D++%5C%5C++%3D++%5Cfrac%7B4%2812+-++%5Csqrt%7B2%7D+%29%7D%7B32%7D++%5C%5C++%3D++%5Cfrac%7B%2812+-++%5Csqrt%7B2%7D%29+%7D%7B8%7D+)
hope it helps...
hope it helps...
Similar questions